EFFECT OF INSTRUCTIONAL MATERIALS IN TEACHING SOCIAL STUDIES EDUCATION - JYOTI BHARTI (International Journal of Multidisciplinary Research and Studies, 2020)
Education and the act of instructing it are both vital considerations for educators who are operating in professional capacities. Learning is a challenging process, but one definition of it characterizes it as a shift in attitude and a change in behaviour that is largely stable over time. This definition describes learning as a shift in attitude and a change in behaviour. This definition admits that the process of learning may be challenging. This shift in mindset and way of behaving is brought about as a direct result of being exposed to new conditions. Learning is something that can take place as a consequence of newly learned skills, knowledge, observation, facts, principles, newly gained information, and other things that are similar in nature. (Adeyanju, 1997) It is possible to improve one’s capacity to learn by utilising a range of instructional materials since these materials have the ability to excite and encourage students while also capturing their attention for a brief amount of time when they are being educated. The processes of teaching and learning take place in schools with the assistance of a wide array of learning aids and technology, which are collectively referred to as instructional materials. According to Akamobi (1998), instructional materials are any things that are used in classrooms or workshops for the purpose of education or demonstration by both teachers and students. This includes objects that are utilized in the classroom as well as workshops. This term includes all of the many things that are utilized in these kinds of environments.